Associations of snoring frequency and intensity in pregnancy with time‐to‐delivery. Issue 6 (28th September 2018) - Dunietz, Galit Levi; Shedden, Kerby; Schisterman, Enrique F.; Lisabeth, Lynda D.; Treadwell, Marjorie C.; O'Brien, Louise M.
Abstract: Background: Sleep‐disordered breathing (SDB) is linked to adverse pregnancy outcomes. However, little is known about the association of SDB with timing of delivery. We examined the association of snoring frequency, a key SDB marker, and snoring intensity, a correlate of SDB severity, with time‐to‐delivery among a cohort of pregnant women. Methods: In this prospective cohort study, 1483 third trimester pregnant women were recruited from the University of Michigan prenatal clinics. Women completed a questionnaire about their sleep, and demographic and pregnancy information was abstracted from medical charts. After exclusion of those with hypertension or diabetes, 954 women were classified into two groups by their snoring onset timing, chronic or pregnancy‐onset. Within each of these groups, women were divided into four groups based on their snoring frequency and intensity: non‐snorers; infrequent‐quiet; frequent‐quiet; or frequent‐loud snorers. Cox proportional hazard regression models were used to investigate the association between snoring frequency and intensity and time‐to‐delivery, adjusting for maternal characteristics. Results: Chronic snoring was reported by half of the pregnant women, and of those, 7% were frequent‐loud snorers. Deliveries before 38 weeks' gestation are completed occurred among 25% of women with chronic, frequent‐loud snoring. Compared with pre‐pregnancy non‐snorers, women with chronic frequent‐loud snoring had an increased hazard ratio for delivery (adjusted hazard ratio 1.60, 95% confidence interval 1.04, 2.45). Conclusions: Snoring frequency and intensity is associated with time‐to‐delivery in women absent of hypertension or diabetes. Frequent‐loud snoring may have a clinical utility to identify otherwise low‐risk women who are likely to deliver earlier.